A revision of the genus Eutetrapha Bates (Coleoptera: Cerambycidae: Lamiinae: Saperdini) - Lin, Mei-Ying; Bi, Wen-Xuan; Yang, Xing-Ke (Zootaxa, 2017)
A revision of the genus Eutetrapha Bates, 1884 is presented. Four new species are described from China: E. parastigmosa Lin & Yang, sp. nov. from Hubei, Chongqing and Shaanxi; E. tianmushana Lin & Bi, sp. nov. from Zhejiang; E. shaanxiana Lin & Yang, sp. nov. from Shaanxi, Hubei, Gansu; and E. gui Lin & Yang, sp. nov. from Hainan. Eutetrapha virides Pu & Jin, 1991 is transferred to the genus Paraglenea, and Glenea ocelota Bates, 1873 is transferred from Eutetrapha to Saperda (Lopezcolonia). Eutetrapha laosensis is newly recorded from India and Myanmar, while Eutetrapha flavoguttata Pu & Jin, 1991 is newly recorded from Myanmar. India and Myanmar represent new country records for Eutetrapha. Twenty-one taxa are recognized in the genus Eutetrapha, and a key to the described species of the genus is presented.